Professional action competences through experiences with augmented reality - Diaz-Noguera, María Dolores; Hervas-Gomez, Carlos; De-La-Calle, Ana María (Journal of Turkish Science Education, 2019)
This empirical study presents university students‟ perceptions of professional competences through the use of such technologies as Augmented Reality (AR). The possibilities offered by this technology allow designing educational environments with different contexts that involve non-traditional practices. An online questionnaire was used to gather the data about their opinions of the use of the AR and the factors supporting the development of good professional practices. The sample consisted of 1920 students from the departments of Early Childhood Education, Primary Education and Pedagogy in the 2015/16 and 2016/17 academic years. To analyse the data, the statistical software SPSS 23.0TM was used. Descriptive, inferential and multilevel analyses were conducted. Three researchers analyzed and categorized the students‟ comments, suggestions, opinions and critics before and after the teaching intervention with the AR. Then, Cohen‟s kappa of 0,70 coefficient was used to calculate interrater reliability value. The results indicate that we must improve our learning design by incorporating simplicity and flexibility to it. On the other hand, we have managed to activate the professional skills of our students. We propose improvements in relation to the activity that should be intuitive, comfortable and easy. We add that personalized work is a very relevant aspect.
Keywords: Augmented reality; good educational practices; higher education; inclusive ecosystem; teaching attitudes